P7 Getting it right first time: CTCA first in gp patients referred to RACPC – is it feasible?. (21st September 2022) - Graby, John; Murphy, David; Metters, Rhys; Parke, Kady; Jones, Samantha; Ellis, Dawn; Khavandi, Ali; Carson, Kevin; Lowe, Rob; Rodrigues, Jonathan CL
Abstract : Objective: Since rapid access chest pain clinics (RACPC) were established to streamline stable chest pain assessment, CT coronary angiography (CTCA) has become the recommended investigation for patients without known coronary artery disease (CAD), with well-defined indications. This single-centre retrospective study assessed the feasibility of upfront GP-led CTCA prior to RACPC. Methods: Electronic records for RACPC pathway patients without pre-existing CAD were reviewed from September - October 2019. Feasibility assessments included appropriateness for RACPC, clinical data recorded via referral versus RACPC assessment for defining CTCA indication and safety, and a comparison of the actual versus hypothetical pathways, impact on timelines and hospital encounters. Results: 106/172 patients screened met inclusion criteria, mean age 61 (±14) and 51% female. 102 (96%) referrals were 'appropriate'. No safety concerns were identified to preclude a CTCA-first strategy. The hypothetical pathway increased CTCA requests versus RACPC (84 vs 71), whilst improving adherence to guidelines and off-loading other services. 23 patients (22%) had no CAD, representing cases where one hospital encounter may be sufficient, which extrapolates to 138 less RACPC appointments annually (£21, 666 in current NHS tariffs). The hypothetical pathway would have reduced referral-to-diagnosis by at least a median of 27 days (IQR 14–33). Conclusion: A hypothetical CTCA-first pathway would have been feasible and safe in a real-world RACPC patient cohort without pre-existing CAD. This novel strategy would have increased referrals for CTCA, whilst streamlining patient pathways by accelerating time to diagnosis and reducing hospital encounters whilst improving NICE guidance adherence.